Ocular Hypertension Drives Remodeling of AMPA Receptors in Select Populations of Retinal Ganglion Cells - Sladek, Asia L.; Nawy, Scott (Frontiers in Synaptic Neuroscience, 2020)
AMPA-type glutamate receptors in the CNS are normally impermeable to Ca2+, but aberrant expression of Ca2+-permeable AMPA receptors (CP-AMPARs) occurs in pathological conditions such as ischemia or epilepsy, or in degenerative diseases such as ALS. Here we show that select populations of retinal ganglion cells (RGCs) similarly express high levels of CP-AMPARs in a mouse model of glaucoma. CP-AMPAR expression increased dramatically in both On sustained alpha and Off transient alpha RGCs, and this increase was prevented by genomic editing of the GluA2 subunit. On sustained alpha RGCs with elevated CP-AMPAR levels displayed profound synaptic depression, which was reduced by selectively blocking CP-AMPARs, buffering Ca2+ with BAPTA, or with the CB1 antagonist AM251, suggesting that depression was mediated by a retrograde transmitter which might be triggered by influx of Ca2+ through CP-AMPARs. Thus, glaucoma may alter the composition of AMPARs and depress excitatory synaptic input in select populations of RGCs.